2016
DOI: 10.7314/apjcp.2016.17.s3.39
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Incidence of Common Cancers in Iran

Abstract: Cancer is a major public health problem in Iran. The aim of this study was to evaluate trends in incidence of ten common cancers in Iran, based on the national cancer registry reports from 2004 to 2009. This epidemiological study was carried out based on existing age-standardized estimate cancer data from the national report on cancer registry/Ministry of Health in Iran. The obtained data were analyzed by test for linear trend and P ≥ 0.05 was taken as the significant level. Totals of 41,169 and 32,898 cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 13 publications
(16 reference statements)
1
18
1
Order By: Relevance
“…The correlation between ageing and cancer is well represented in BC, as with advancing age, the risk of developing BC increases, and patients’ clinical presentation and outcomes worsen [17] . In agreement with previous reports, 86% of all BC cases were aged >50 years [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The correlation between ageing and cancer is well represented in BC, as with advancing age, the risk of developing BC increases, and patients’ clinical presentation and outcomes worsen [17] . In agreement with previous reports, 86% of all BC cases were aged >50 years [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] .…”
Section: Discussionsupporting
confidence: 91%
“…Cancer is a leading cause of morbidity and mortality in the USA and results in a high economic burden [12] . Likewise according to published articles, cancer could be considered as a major public health problem in Iran too [13] , [14] , [15] . Furthermore, BC is reported to be the ninth most common cancer and the fourteenth leading cause of death from cancer worldwide [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is one of the most common non-communicable diseases and the second cause of death in Iran. The rate and prevalence of cancer has considerably increased over the recent years due to a myriad of factors such as aging population, industrialization, changes in the lifestyle, and environmental changes [1]. Skin cancer is one of the most common types of cancer in Iran with 7000 new diagnoses every year.…”
Section: Introductionmentioning
confidence: 99%
“…According to Iran National Cancer Registry in 2014, CC with the total incidence rate of 9861 cases in 30 Provinces of Iran (Qom Province excluded) and the age-standardized rate of 16.57 and 11.86 per 100,000 was the fifth most prevalent cancer among men and the second one among women. Different studies indicated an increase in the incidence of this disease in recent years in Iran [3][4][5]. Cancer survival rate (SR) is a widely used indicator for physicians, patients and health policymakers, and reflects the prognosis of cancer patients [6].…”
mentioning
confidence: 99%